Isolated Cavities Dominate Greenland Ice Sheet Dynamic Response to Lake Drainage. Issue 19 (5th October 2021) - Mejia, J. Z.; Gulley, J. D.; Trunz, C.; Covington, M. D.; Bartholomaus, T. C.; Xie, S.; Dixon, T. H.
Abstract: Seasonal variability in the Greenland Ice Sheet's (GrIS) sliding speed is regulated by the response of the subglacial drainage system to meltwater inputs. However, the importance of channelization relative to the dewatering of isolated cavities in controlling seasonal ice deceleration remains unsolved. Using ice motion, moulin hydraulic head, and glaciohydraulic tremor measurements, we show the passing of a subglacial floodwave triggered by upglacier supraglacial lake drainages slowed sliding to wintertime background speeds without increasing the hydraulic capacity of the moulin‐connected drainage system. We interpret these results to reflect an increase in basal traction caused by the dewatering of isolated cavities. These results suggest the dewatering of isolated parts of the subglacial drainage system play a key role in driving seasonal slowdowns on the GrIS. Plain Language Summary: Meltwater produced on the surface of the Greenland Ice Sheet reaches the bed by flowing into crevasses or moulins, vertical holes that connect to the ice sheet's base. Early in the summer, meltwater that reaches the bed increases water pressures within the drainage system underneath the ice sheet, increasing sliding speeds. However, later in the summer, ice sliding speeds often slowdown despite continued meltwater inputs. While these slowdowns have been attributed to the growth of subglacial conduits, recent observations suggest the drainage of hydraulically isolated cavities—pockets of water formed by ice sliding over bedrock bumps—may instead be responsible. Here, we measure surface ice motion and water pressures within moulins located several kilometers away from rapidly draining supraglacial lakes. We show the passing of a floodwave underneath the ice sheet slowed sliding to wintertime speeds without enlarging subglacial channels connected to our instrumented moulin. Instead, our results indicate the drainage of isolated cavities may be responsible for slowdowns that occur during the melt season. Accordingly, our results, similar to others, suggest increased channelization of the subglacial drainage system appears unlikely to buffer GrIS ice velocity against future meltwater inputs. Key Points: We monitored ice motion and moulin hydraulic head along the path of a subglacial flood wave following upglacier supraglacial lake drainages Initial and subsequent slowdowns after the lake drainage were not caused by increased efficiency of the moulin‐connected drainage system Our observations suggest floodwaters induced persistent basal traction increases by dewatering isolated cavities over large areas of the bed